Phenolic Profile and Antimicrobe of the Asplenium Nidus L. from Mount Gumitir, Jember, East Java, Indonesia - Dwi Setyati; Robi’atul Adawiyah; Tri Ratnasari; Mukhamad Su'udi; Fuad Bahrul Ulum (BIOEDUKASI, 2023)
Mount Gumitir, Jember, East Java has a high number of wild flora for new medicinal resources. Asplenium nidus is a medicinal ferns that abundant in the area. This research aimed to measure the phenolic compound of the lamina and midrib sample of A. nidus from two different locations and the antimicrobial activity of the crude extract of fresh and dry sample. The phenolic compounds of flavonoid and phenol were detected using quercetin and Folin-Ciocalteu reagent respectively. The quantitative analysis of phenolic compounds was conducted based on absorbance detection using a spectrophotometer. The antimicrobial assay was applied with the agar diffusion method against the gram-positive bacterium Staphylococcus aureus and gram-negative bacteria Escherichia coli. The result indicated that all samples of A. nidus contained flavonoid and phenol with a higher concentration in the lamina. The crude extract of A. nidus from Gumitir has higher phenolic compounds compared to the sample from Garahan. The crude extract presented bactericide activity against the two pathogenic bacteria. The higher antimicrobial activity was observed from the dry leaves sample. The phenolic compound of A. nidus might become a potential resource for the treatment of multidrug-resistant bacteria since their bactericide activities differ from traditional antibiotics.